Mengintip pesona alam dan kearifan lokal: Destinasi ‎pariwisata Desa Poncokusumo Kabupaten Malang - Nurchasanah, Risma Siti (Maliki Interdisciplinary Journal, 2023)
This article reviews the potential for ecotourism and local wisdom in Poncokusumo Village, as a real example of integration between sustainable tourism and local culture. Ecotourism, which emphasizes nature conservation and a sustainable approach, is combined with local wisdom which includes cultural values, traditions and knowledge of the local community. The results of the study show that Poncokusumo Village has an amazing natural charm and local wisdom that is reflected in the traditions and culture of the community. In this context, the article supports the idea that sustainable tourism development must take both factors into account. The research was conducted through the observation method, observing the interaction of nature and culture in the tourism context. Tourism destinations in the village include the Ledok Ombo Camping Ground, Jamun Spot Sunset, Banyu Guest, Banyu Biru, and Taman Kali Lesti, with facilities that support tourism activities. Poncokusumo Village has achieved harmony between natural charm and local wisdom, providing valuable lessons for the development of sustainable tourism in Indonesia.